THE DEVELOPMENT OF AFFECTIVE DOMAIN ASSESSMENT INSTRUMENTS ABOUT THE ENTREPRENEURSHIP OF STUDENTS IN HIGH SCHOOL - Theresia Anggraini; Ari Saptono; Aditya Pratama (Jurnal Pendidikan Ekonomi, Perkantoran, dan Akuntansi, 2022)
This research aims to develop and produce good affective assessment instruments, as well as meet the criteria of validity and reliability. This research uses research and development (R&D) methods. Data collection with questionnaires in the form of several statements about the entrepreneurial spirit, consisting of 5 dimensions, namely motivation to excel, creative thinking, independence, business risk-taking, and leadership. In this study, respondents were students of grade XI IPS at SMA Negeri 35 and SMA Negeri 7 Jakarta. Of the 37 items developed, 36 were conducted limited trials and final field tests. Based on the validity test with Product Moment correlation, and reliability with Alpha Cronbach it is obtained that the 36 statements are valid and reliable. Furthermore, instrument standardization is carried out with CFA factor analysis, and as many as 12 items are fit, valid, and reliable. Then, the entrepreneurial spirit level of students of SMA Negeri 35 and SMA Negeri 7 Jakarta, out of 5 categories was in the moderate category (7.04%), high (48.36%) and very high (44.60%).